2022
DOI: 10.1007/s11356-022-21717-6
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and identification of relative poverty level of pastoral areas: an analysis based on spatial layout

Abstract: Pastoral areas are the key difficulty in China’s pursuit of common prosperity and a key region for China to build the northern ecological safety barrier and to realize the Two Centenary Goals. It is of great significance to scientifically evaluate the quality of rural life (QRL), measure the relative poverty level (RPL), and identify the relatively poor areas, making it possible to dock poverty elimination with rural revitalization. Based on the socio-economic data of 18 pastoral areas in Inner Mongolia, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…From the viewpoint of the internal urban environment, the imbalance and inadequacy of the development of DE between urban and rural areas is an important reason for the digital divide (Lin et al, 2022). The urban DE is developing faster than the rural DE, resulting in a mismatch between digital technology and digital infrastructure in rural areas, creating a digital divide that is not conducive to the DE playing a positive role in the EWP of rural areas (Liu and Zhou, 2023).…”
Section: Intra-urban Environmental Factor: Level Of Rural Revitalizationmentioning
confidence: 99%
“…From the viewpoint of the internal urban environment, the imbalance and inadequacy of the development of DE between urban and rural areas is an important reason for the digital divide (Lin et al, 2022). The urban DE is developing faster than the rural DE, resulting in a mismatch between digital technology and digital infrastructure in rural areas, creating a digital divide that is not conducive to the DE playing a positive role in the EWP of rural areas (Liu and Zhou, 2023).…”
Section: Intra-urban Environmental Factor: Level Of Rural Revitalizationmentioning
confidence: 99%
“…China is a family-based society, and in addition to individual characteristics, family elements also affect poverty [ 39 ], such as per capita household income, proportion of agricultural income, and household consumption, and the external environment, including the individual's family environment, can also have an impact on poverty, such as regional financial support policies [ 40 ], and household capital perspectives such as house type [ 41 ] and the value of durable goods [ 42 ]. In addition to the above dimensions, scholars have also explored poverty status from the perspective of psychological conditions, such as confidence and stress [ 43 ]; geographic perspective, such as rain [ 44 ]and sunlight [ 45 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…formal sector = 1, informal sector = 0 Cichello [ 127 ] migrant_worker Whether the respondent is currently working outside the home, yes = 1, no = 0 Peng [ 128 ] farm_forest Whether the respondent's family is engaged in agriculture, forestry, animal husbandry and by-fishing, yes = 1,no = 0 Ghimire [ 129 ] major_thing Whether there was a major incident in the household of the respondent in the previous year, yes = 1,no = 0 Healey [ 130 ] loan The per capita loan amount of the respondents' households Burgess [ 131 ] total_house_property Respondent's household total expenditure Bartoşová [ 132 ] food_cost Respondent's household food expenditure Bartoşová [ 132 ] medicel_cost Respondent's household medical expenditure Bartoşová [ 132 ] consume_cost Respondent's household consume expenditure Bartoşová [ 132 ] education_cost Respondent's household education expenditure Lin [ 133 ] Individual Characteristics Production_risk Respondent's family dependency ratio Allen [ 134 ] CFPS water Respondents' domestic water consumption Adetayo [ 135 ] fuel Respondent's living and cooking fuel ...…”
Section: Tablementioning
confidence: 99%
“…Literature [12], in order to study the quantitative measurement of multidimensional poverty regression in Chinese rural households, combined the worker neural network and multidimensional measurement model to assess the dynamic evolution of multidimensional regression poverty in rural households in China, showed that the per capita annual net income is the main factor leading to the decline of the multidimensional poverty rate, and put forward relative recommendations. Literature [13] used socio-economic data from 18 pastoral areas in Inner Mongolia as the basis for measuring the ecological carrying capacity of pastoral areas using the natural breakpoint method, evaluating the ecological carrying capacity using the spatial layout theory, identifying the relatively impoverished areas in Inner Mongolia and establishing an early warning mechanism for large-scale return to poverty, with the aim of reducing the comprehensive RPL and realizing the revitalization of the countryside.…”
Section: Literature Reviewmentioning
confidence: 99%